Ketahanan Beton fc’ 22,5 MPa Terhadap Kondisi Air Kota Palangka Raya - Norseta Ajie Saputra; Noviyanthy Handayani (Rekayasa Sipil, 2020)
Palangka Raya is a city where almost a part of the area is peatland with peat water with an acidity level of around 4.0 - 5.0 which can make concrete become porous and cause damage. This study is to determine the effect of peat water, Kahayan river water, and PDAM water on the compressive strength of concrete. In this study, the immersion of concrete samples was carried out for 28 days and 60 days. The measurement results are known that the pH of peat water is 4.0 while the pH of Kahayan river water and PDAM water is 5.0.From the results note that in the 28 days immersion, peat water concrete has increased in compressive strength while concrete in Kahayan river water and PDAM water has decreased in compressive strength. However, during the 60 days immersion the peat water concrete decreased in compressive strength to 20,638 MPa (17.31%). Whereas the Kahayan river water and PDAM water in the 60 days immersion experienced an increase in compressive strength values of 31,687 MPa (26.96%) and 27,696 MPa (10.98%). From these results, it can be concluded that the Kahayan river water with pH = 5.0 does not make the concrete lose its strength and can survive in an acidic environment.